Groundwater quality evaluation for drinking and industrial purposes. A case study in Northeastern Iran. Issue 17 (23rd December 2022) - Mohammadi, Ali Akbar; Morovati, Maryam; Najafi Saleh, Hossein; Ghale Askari, Sahar; Ghaderpoori, Mansour; Shams, Mahmoud; Kalteh, Safa; Sadeghi, Shahram
ABSTRACT: Groundwater is an important source of drinking water in arid areas, and its quality can affect human health. Groundwater quality investigations were performed to assess the physicochemical quality parameters of groundwater of Northeastern Iran, to determine its suitability for drinking purposes based on the drinking water quality index (WQI). The suitability for drinking purposes was evaluated by comparing the physicochemical parameters of groundwater in the study area with those prescribed by the World Health Organisation (WHO) and standard Code of 1053 (Iran National Standard). Five indices were considered to determine water suitability for industrial purposes. A total of 51 water samples were taken based on standard methods (in September 2017 and April 2018) for the measurement of the most important physicochemical parameters, including major anions, cation, pH, total dissolved solids (TDS), alkalinity, and electronic conductivity. The WQI values showed that 30.65 and 65.08% of the groundwater samples were in the excellent and very good water quality categories, respectively. Due to the human impact, 4.07% of the samples were in the poor range category. The results demonstrated that based on the Langelier saturation index (LSI), 34.9% of the water distribution network was corrosive. Furthermore, the Larson empirical index showed that 17.46% of the network had a corrosive potential for the occurrence of holes and leakages. The aggressiveness index (AI) categorised 20.6% of the groundwater resource into a moderately aggressive condition. The high values of WQI in several groundwater samples of Neyshabur indicated that water is suitable for direct domestic consumptions. The results also showed that drinking water tends to be corrosion in the studied area.